SAL. MODEL: USE OF CHILDREN’S SONGS AS LANGUAGE - Lani Indriyani; Nurul; Az-Zahra, Siti Fatimah; Salwa Aqilah, Wardah (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Elementary school learning faces challenges in creating an effective and enjoyable learning atmosphere. This study aims to explore the implementation of the singing and learning model using children's songs as a communication medium in elementary school learning, which includes: (1) teachers' understanding and perceptions of the concept of children's songs as language or communication tools; (2) implementation and practice of the learning model; (3) impacts and challenges faced; and (4) evaluation and development recommendations. The study employed a qualitative approach with a descriptive method through in-depth interviews with teachers at SDIT Mutiara Insan. Data were analyzed using content analysis techniques. The results show that teachers understand children's songs as effective educational communication tools, not merely entertainment. Implementation is carried out by selecting songs according to the material and integrating them into learning explanations. Positive impacts are evident in increased motivation, student activeness, focus, and the creation of a pleasant classroom atmosphere. However, there are challenges in selecting appropriate songs, material integration, and attracting student interest. For optimization, collaboration among teachers, pedagogical skills training, institutional support, and integration with other learning approaches are needed. The singing and learning model has proven to be an effective and enjoyable alternative learning strategy for implementation in elementary schools.